Clinical Neurology - Christopher G. Goetz, MD (2007)
The third edition of Textbook of Clinical Neurology has been prepared for all clinicians directly involved with patients with neurological diseases: neurologists, neurosurgeons, internists, psychiatrists, and family practitioners, whether senior clinicians, residents, or students. Building on the successes of the prior editions (1999 and 2003), we have updated materials and added several new areas of discussion to cover the breadth of contemporary clinical neurology.